PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PENGGUNAAN LAYANAN JASA PADA MELIA LAUNDRY & DRY CLEANING OUTLET HAYAM WURUK - I Wayan Sugiartana; Cokorda Istri Mas Kusumaningrat (Bajang Institute, 2026)
Brand image is very important in determining consumer decisions to use laundry & dry cleaning services, where an effective brand image can build the character of a company's products. Melia Laundry & Dry Cleaning has a good image among consumers which is using premium quality and environmentally friendly laundry chemicals. In this research, researchers can use quantitative data types, and researchers also use primary data sources and secondary data sources. The data analysis technique that the researcher used was SPSS type 26. The number of samples in this study was 68 respondents. The selection of respondents used an accidental or accidental sampling technique (Sugiyono 2012) which means it was based on someone who by chance had or was currently using the services of Melia Laundry & Dry Cleaning Outlet Hayam Wuruk. By using the SPSS method it can be seen that the t-count value is 7.518 > t-table 1.997. In accordance with the criteria, if t-count > t-table then H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between brand image on the decision to use services.